Age-group-specific association of oral health and systemic health on cognitive function: a cross-sectional study of Korean elders - Jae-Eun Sin; Hye-Sung Kim; Inseong Hwang; Miwha Noh (BMC, 2023)
Abstract Background Although the importance of oral and systemic healthcare for elderly people is increasing owing to the rapid ageing of the population in South Korea, studies on the relationship between oral health, systemic health, and cognitive function, as well as on the prediction of cognitive function by oral and systemic health depending upon age groups are lacking. Methods We included 5,975 out of 6,488 participants from the 8th wave of the Korean Longitudinal Study of Aging (KLoSA) panel data, divided the participants into three age groups, and performed a hierarchical multiple linear regression analysis to explain cognitive function with four types of predictors: oral health status, sociodemographic factors, objective health status, and subjective health status. Results Oral health status was positively correlated with systemic health status and cognitive function. Of all ages over 54, cognitive function was significantly predicted by oral health variables, such as the number of functional teeth, masticatory ability, and Geriatric Oral Health Assessment Index (GOHAI); sociodemographic variables, such as age, sex, education level, and residence; and systemic health variables, such as diagnosis of diabetes mellitus, cancer or malignant tumours, cerebrovascular disease and rheumatoid arthritis, depressive symptom, and self-rated health status. Oral health variables explained cognitive function differently by age group; GOHAI appeared important predictor in the group aged < 75 years, whereas the number of functional teeth did in the group aged ≥ 75 years. Educational level, masticatory ability, depressive symptoms, and self-rated health status were pivotal factors age-independently. Conclusions The general and age-group-specific association between oral health, systemic health, and cognitive function were confirmed, suggesting that age-group-specific oral healthcare should be emphasized for the effective management of systemic and cognitive health in the elderly group.